Hubungan Antara Struktur Kepemilikan, Corporate Governance, dan Nilai Perusahaan: Suatu Kajian Konseptual - Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
This research is a study koseptual studying relation between practice of corporategovernance and company value where related to wedge(control rights - cash flowrights). Besides, studies relation between ownership of stock by the side ofstrangers foreigners but Indonesia original(ATI) and ownership of stock by theside of strangers foreigners non-Indonesia(ANI)to company value and practiceof corporate governance. Based on review literature from former research andbased on critical idea it is indicated that ownership structure hardly influencesrelation between practice of corporate governance and company value. Besides,to know relation between ATI and ANI with company value it is indicated thatownership of stock ATI will had lower influence to company value if it iscompared to ownership of stock ANI. Side other, to know the relation of ATI andANI with corporate governance, indicated ownership of stock ATI to have lowermotivation than ownership of stock ANI to execute practice of corporategovernance carefully.